Keabsahan Klausula Eksonerasi dalam Perjanjian Digital Aplikasi Ride-Hailing Ditinjau dari Undang-Undang Perlindungan Konsumen - Sidiq, Ananda Maulana; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Digital agreements in ride-hailing applications via clickwrap mechanisms often contain exculpatory clauses that waive the platform's liability for consumer losses. This normative legal research analyzes the validity of such clauses under the Consumer Protection Law (UUPK) using statutory, conceptual, and case approaches. The results indicate that although these electronic contracts fulfill the validity requirements of Article 1320 of the Indonesian Civil Code and the ITE Law, the unilateral inclusion of exculpatory clauses violates the prohibition on restrictive standard clauses under Article 18 of the UUPK, rendering them null and void. The legal implications are multi-layered, encompassing the civil invalidity of the clause, administrative sanctions such as business license revocation, and criminal penalties for non-compliant businesses.